(untitled) (Pedagogy of Higher and Secondary Education, 2022)
In this article, the author reveals the place and role of extracurricular activities in the twelve-year education system. The basic directions of work with children of different age groups, given their age. The author argues that properly organized classwork in English develops the communication skills of schoolchildren